Composite high-temperature-resistant filter felt and preparation method thereof
By using a base cloth layer blended with basalt fiber and polyimide fiber in the filter felt and a composite layer of ceramic fibers, silicon carbide nanowires and polytetrafluoroethylene modified fibers, combined with gradient needle puncture and plasma treatment processes, the problem of insufficient high temperature resistance in high temperature and radiation environments is solved, and efficient high temperature resistance and radiation resistance are achieved.
Patent Information
- Application Number
- CN202510386290.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-31
AI Technical Summary
Traditional filter felts have insufficient high temperature resistance in high temperature and radiation environments, resulting in aging, fracture and reduced filtration efficiency.
A base fabric layer blended with basalt fibers and polyimide fibers is used, and a composite material layer of ceramic fibers, silicon carbide nanowires and polytetrafluoroethylene modified fibers is used to form a high-strength, high-temperature and radiation-resistant filter felt through gradient needle puncture and plasma treatment process.
The high temperature and radiation resistance of the filter felt is significantly improved, so that its strength retention rate is significantly improved at 300°C, and it shows excellent radiation resistance in a radiant environment.
Smart Images

Figure CN119896912A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of filter materials, in particular to a composite high-temperature resistant filter felt and a preparation method thereof. Background Art
[0002] Filter felt, as a highly efficient filter material, plays an important role in the solid-liquid separation and gas purification processes in various industries. It is usually made of high-quality fiber materials, which are interwoven to form an extremely fine and uniform pore structure. This unique structure gives the filter felt excellent filtering performance, and can accurately intercept and separate various tiny particles, from impurities in industrial wastewater to dust in the air, with a filtering accuracy of up to micron level. In terms of materials, filter felts cover a variety of types. For example, chemical fiber filter felts, with their good chemical corrosion resistance, can adapt to filtering work in harsh chemical environments such as strong acids and alkalis; while glass fiber filter felts have excellent high temperature resistance and can operate stably in high temperature conditions to ensure that the filtering effect is not affected by temperature fluctuations. In terms of performance, it not only has high filtering efficiency, but also has a strong dirt holding capacity, can work continuously for a long time without frequent replacement, greatly reducing maintenance costs and production interruption risks.
[0003] In modern industrial production, industries such as steel smelting, chemical industry, and electric power often produce high-temperature dusty gases. The temperature of these gases is often higher than 300°C, and they may be accompanied by radiation. In such an environment, traditional filter felts are not resistant to high temperatures, and are prone to fiber aging and breakage, which leads to a sharp drop in filtration efficiency. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a composite high-temperature resistant filter felt and a preparation method thereof, which can significantly improve the high-temperature resistance and radiation resistance of the filter felt.
[0005] To achieve the above object, the present invention provides the following technical solution: a composite high temperature resistant filter felt and a preparation method thereof, comprising the following structural layers: Base fabric layer: woven from basalt fiber and polyimide (P84) fiber, with a gram weight of 400g / m²-600g / m²; Composite material layer: Ceramic fiber, silicon carbide nanowire and polytetrafluoroethylene (PTFE) modified fiber are compounded on both sides of the base fabric layer through gradient needle punching process. The total weight of the composite material layer is 200g / m²-350g / m²; Surface functional layer: It is composed of a coating of polytetrafluoroethylene emulsion and silicon carbide nanoparticles, with a thickness of 5μm-15μm and a surface pore size of 0.5μm-2μm.
[0006] Preferably, the weight ratio of basalt fiber to polyimide fiber in the base fabric layer is 3:1-5:1, and the fiber fineness is 1.5D-3D (D is denier).
[0007] Preferably, the components of the composite material layer include, by weight: 40-60 parts of ceramic fibers, 10-20 parts of silicon carbide nanowires, 20-30 parts of polytetrafluoroethylene modified fibers, 1-3 parts of silane coupling agents, and 0.5-1 parts of dispersants.
[0008] Preferably, the polytetrafluoroethylene modified fiber is a product of PPS fiber impregnated with polytetrafluoroethylene emulsion, and the impregnation liquid rate is 50%-120%.
[0009] Preferably, the particle size of the silicon carbide nanoparticles in the surface functional layer is 50-200 nm, and the solid content of the polytetrafluoroethylene emulsion is 55-65 wt %.
[0010] Preferably, the method comprises the following steps: S1. Preparation of base fabric: basalt fiber and polyimide fiber are blended and woven into base fabric, and subjected to heat setting treatment at a temperature of 200°C-250°C for 5min-10min; S2. Pretreatment of the composite material layer: After mixing the ceramic fiber, silicon carbide nanowire and polytetrafluoroethylene modified fiber, the surface of the ceramic fiber is activated by plasma at a power of 200W-400W for 3-5min. S3, gradient needling composite: Lay the pretreated composite material layer on both sides of the base fabric, and perform pre-needling and main needling in sequence, with a pre-needling density of 300 times / cm²-500 times / cm² and a main needling density of 800 times / cm²-1000 times / cm²; S4. Surface functional layer coating: Mix polytetrafluoroethylene emulsion and silicon carbide nanoparticles and spray them on the surface of the composite material layer. After drying at 100°C-120°C, sinter at a high temperature of 300°C-350°C for 2min-5min to obtain filter felt.
[0011] Preferably, the gas for plasma treatment is a mixed gas of argon and oxygen with a volume ratio of 4:1.
[0012] Preferably, it also includes an impregnation enhancement treatment: the composite filter felt is impregnated in a dispersion containing silica sol, the silica sol concentration is 5%-10%, the impregnation time is 10min-20min, and then high-temperature curing is carried out at 250℃-280℃ for 3min-5min.
[0013] Compared with the prior art, the present invention provides a composite high-temperature resistant filter felt and a preparation method thereof, which have the following beneficial effects: through the composite system of ceramic fiber and SiC nanowire, the prepared filter felt has a higher strength retention rate at 300°C, which is also significantly higher than that without gradient needle punching composite, reflecting that the combination of gradient needle punching composite promotes further improvement of high-temperature resistance; the surface layer has significantly improved radiation resistance properties after plasma treatment process and SiC nanoparticles, and the plasma treatment process and SiC nanoparticles have a synergistic promoting effect on radiation resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a bar graph of the strength retention rate of a composite high temperature resistant filter felt at 300°C; Figure 2 This is a line graph of the elongation loss at break of a composite high-temperature resistant filter felt after γ irradiation. DETAILED DESCRIPTION
[0015] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0016] Basalt fiber: It is derived from natural ore and is made by high-temperature melting and drawing. It has high strength and high modulus, and can withstand large external forces without breaking easily. Its outstanding high-temperature resistance makes its structure stable in high-temperature environments without softening or deformation. It has good chemical stability and can effectively resist corrosion from a variety of chemical substances. In the preparation of filter felt base fabric, it is blended with P84 fiber to build a solid strength foundation for the base fabric, ensuring the structural integrity of the base fabric under high-temperature conditions. P84 fiber: It is a high-performance synthetic fiber with excellent high temperature resistance and can be used for a long time in high temperature environment. It has strong chemical resistance and can resist corrosion from common chemicals. It also has flame retardant properties to reduce the risk of fire. When blended with basalt fiber, it can effectively improve the flexibility of the base fabric and overcome the rigidity deficiency of basalt fiber, making the base fabric easier to process and shape while having high strength, and more comfortable in actual use. Ceramic fiber: It is known for its excellent high temperature resistance and can withstand temperatures exceeding 1000°C. It has good thermal insulation properties and can effectively prevent heat transfer. It has stable chemical properties and is not prone to chemical reactions in complex chemical environments. In the composite material layer of the filter felt, it is the core material to improve the overall high temperature resistance. It works in synergy with other materials to ensure that the filter felt can maintain high strength after long-term use at 300°C. SiC nanowires: nanometer-sized and extremely fine in diameter. With a high specific surface area, they can greatly increase the contact area with other materials and promote interaction. They have high strength and excellent thermal stability, and are stable at high temperatures. In filter felts, they can be combined with ceramic fibers to optimize the mechanical properties and thermal conductivity of the composite material layer, and participate in the construction of micro-nano hydrophobic structures in the surface functional layer, making a significant contribution to improving the self-cleaning function. PTFE modified fiber (PPS base material impregnation): PTFE is polytetrafluoroethylene, which has extremely excellent chemical stability and hardly reacts with any chemical substances. It has super corrosion resistance and can withstand harsh chemical environments such as strong acids and alkalis. The low friction coefficient makes its surface smooth and not easy to adhere to impurities. After impregnation with PPS as the base material, the comprehensive performance of the fiber is further improved, which has an important impact on the structural stability and overall performance in the composite material layer. PTFE emulsion: It is formed by dispersing PTFE in water. It has good fluidity and film-forming properties and can be evenly coated on the surface of the filter felt. After film formation, it has waterproof and oil-proof properties and can effectively prevent the adhesion of liquids and oil stains. In the coating of the surface functional layer, it is matched with SiC particles of different particle sizes to jointly construct a micro-nano hydrophobic structure, which significantly reduces the adhesion of dust on the surface of the filter felt and reduces the difficulty of cleaning. Silica sol: It is a colloidal solution of silicate with good permeability. During the impregnation enhancement treatment, it can penetrate into the internal pores of the filter felt and fill the tiny gaps. After curing, it can enhance the bonding force between the layers of materials, significantly improve the overall strength of the filter felt, and at the same time enhance its corrosion resistance and extend the service life of the filter felt.
[0017] Embodiment 1, a composite high temperature resistant filter felt and a preparation method thereof, comprising the following steps: S1. Fabric preparation: basalt fiber and P84 fiber are blended in a ratio of 3:1 (fineness 1.5D), woven into a 400g / m² fabric, and heat-set at 200℃×10min; S2, pretreatment of composite material layer: containing 40 parts of ceramic fiber (diameter 5μm), 10 parts of SiC nanowire (diameter 30nm), 20 parts of PTFE modified fiber (PPS substrate impregnation liquid rate 50%), treated with 200W argon oxygen mixed gas plasma for 3min; S3, gradient acupuncture composite: pre-needling density 300 times / cm², main needling density 800 times / cm² to form a composite layer with a total weight of 200g / m²; S4, surface functional layer coating: 55% solid content PTFE emulsion and 50nm SiC particles (10:1) were mixed and sprayed, pre-baked at 120℃ and sintered at 300℃ for 2min to form a 5μm functional layer; S5. Impregnation reinforcement treatment: impregnate with 5% silica sol for 15 minutes and then cure at 280℃ for 3 minutes.
[0018] Embodiment 2 comprises the following steps: S1. Fabric preparation: Basalt / P84 in a ratio of 4:1 (2D fineness) to make 500g / m² fabric, 225℃×8min for finalizing; S2, composite material layer pretreatment: 50 parts of ceramic fiber + 15 parts of SiC nanowire + 25 parts of PTFE fiber (liquid carrying rate 85%), 300W plasma treatment for 4 minutes; S3, gradient acupuncture composite: 400 times / cm² pre-puncture + 900 times / cm² main puncture to form a 275g / m² composite layer; S4, surface functional layer coating: 60% PTFE emulsion and 100nm SiC (12.5:1) spraying, 110℃ pre-baking + 325℃ sintering for 3min to obtain 10μm functional layer; S5. Impregnation reinforcement treatment: 7.5% silica sol impregnation for 15 minutes + 265℃ curing for 4 minutes.
[0019] Embodiment 3 comprises the following steps: S1. Fabric preparation: 5:1 basalt / P84 (3D fineness) 600g / m² fabric, 250℃×5min setting; S2, composite material layer pretreatment: 60 parts of ceramic fiber + 20 parts of SiC nanowire + 30 parts of PTFE fiber (liquid carrying rate 120%), 400W plasma treatment for 5 minutes; S3, gradient acupuncture composite: 500 times / cm² pre-puncture + 1000 times / cm² main puncture to form a 350g / m² composite layer; S4, surface functional layer coating: 65% PTFE emulsion and 200nm SiC (15:1) spraying, 120℃ pre-baking + 350℃ sintering for 5min to obtain 15μm functional layer; S5. Impregnation reinforcement treatment: 10% silica sol impregnation for 20 minutes + 250℃ curing for 5 minutes.
[0020] In comparative example 1, the base fabric layer is made of pure basalt fiber, and the other steps are the same as those in example 1.
[0021] In comparative example 2, the plasma treatment process is omitted, and other steps are the same as those in example 1.
[0022] In comparative example 3, there are no SiC nanoparticles in the surface layer, and the other steps are the same as those in example 1.
[0023] In comparative example 4, the gradient needling was changed to uniform needling, the needling density was 800 times / cm², and the other steps were the same as those in example 1.
[0024] In Comparative Example 5, no silica sol impregnation treatment was performed, and other steps were the same as those in Example 1.
[0025] Comparative Example 6: Purchase the existing needle-punched filter felt (model HTF-3000) on the market. The specific ingredients are shown in Table 1.
[0026] Table 1 is a table of relevant components of comparative example 6 The nine groups of filter felts in Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4, 5 and 6 were grouped and numbered, respectively, as FH-GLZ1001, FH-GLZ1002, FH-GLZ1003, FH-GLZ1004, FH-GLZ1005, FH-GLZ1006, FH-GLZ1007, FH-GLZ1008 and FH-GLZ1009, and the grouped filter felts were tested for high temperature resistance (strength retention at 300°C) and radiation resistance (elongation loss at break after γ irradiation). For specific test results, see Table 2.
[0027] Table 2 shows the test results of the embodiments and comparative examples on high temperature resistance and radiation resistance Table 3 Test results of dust removal rate, cleaning resistance and corrosion grade performance of the embodiments and comparative examples It can be seen from Table 2 that, in terms of temperature resistance, the strength retention rate of the ceramic fiber and SiC nanowire composite system (Example 2) at 300°C is 93.5%, which is significantly higher than that of the comparative example 4 (84.9%) without the gradient structure. In terms of radiation resistance, after 1000h of γ irradiation, the elongation loss at break of the embodiment group is 4.8%, 3.2%, and 5.1%, respectively, while the radiation resistance of the comparative example 2 without plasma treatment and the one without SiC nanoparticles decreases to varying degrees, indicating that the plasma treatment process and SiC nanoparticles have a synergistic effect on radiation resistance. In terms of self-cleaning effect, the dust stripping rate of the embodiment group containing SiC nanoparticles is better, and the cleaning resistance is significantly lower than that of the comparative example 3, which verifies the synergistic effect of the micro-nano structure. In terms of process innovation, the silica sol impregnation significantly improves the acid corrosion resistance.
[0028] High temperature performance evaluation standard: High temperature performance is divided into three levels with the 300°C strength retention rate as the evaluation index. The excellent level requires a strength retention rate of ≥90%, meeting the requirements for long-term use in high temperature conditions; the qualified level has a strength retention rate between 80% and 89%, requiring regular replacement or downgrading; the substandard level has a strength retention rate of <80%, which cannot pass the high temperature durability test; Test method and data basis: The test method is based on GB / T3923.1-2013 Textile Tensile Properties Test. After the sample is placed in a 300°C constant temperature box for 500 hours, its breaking strength retention rate is measured.
[0029] Radiation resistance performance evaluation standard: Radiation resistance is evaluated by the elongation loss rate at break after γ irradiation, and is divided into three levels. The excellent level requires an elongation loss rate at break of ≤5%, with excellent resistance to radiation embrittlement; the qualified level has an elongation loss rate at break between 6% and 10%, and the irradiation dose must be limited when used; the substandard level has an elongation loss rate at break of >10%, and the material will become brittle and fail after irradiation; Test method and data basis: The test method refers to "ASTM D1876-08 Performance Test of Polymer Materials in Radiation Environment", using a 60Co γ-ray source for 1000h (dose rate 1kGy / h) to measure the change in elongation at break.
[0030] Self-cleaning performance evaluation standard: Self-cleaning performance is evaluated based on dust removal rate and cleaning resistance, and is divided into three levels. The excellent level requires a dust removal rate of ≥98% and a cleaning resistance of ≤2.5kPa, indicating that the micro-nano hydrophobic structure can significantly reduce dust accumulation; the qualified level has a dust removal rate of 90%-97% and a cleaning resistance of 2.6-3.5kPa, and the cleaning frequency needs to be increased during use; the substandard level has a dust removal rate of <90% and a cleaning resistance of >3.5kPa, which may cause dust compaction and filter material blockage.
[0031] Test method and data basis: In terms of test method, the dust stripping rate is based on the "ISO11057 Air Filter Cleaning Performance Test", simulating the dust load (5g / m²) and then pulse cleaning to calculate the mass percentage of residual dust; the cleaning resistance uses a differential pressure gauge to measure the difference in filter resistance before and after cleaning.
[0032] Corrosion resistance performance evaluation standards: No shedding or discoloration during the test indicates excellent interface bonding and sealing, which is excellent (A) grade; slight local shedding during the test requires auxiliary anti-corrosion treatment, which is qualified (B) grade; obvious cracking and powdering occur, and it cannot pass the industrial corrosion environment test, which is unsatisfactory (C) grade.
[0033] Test method and data basis: Corrosion resistance is based on the extended method of "ISO9227 Salt Spray Test". The surface condition is observed after immersion in 10% HCl solution for 72 hours.
[0034] The above are only specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent replacements or modifications made based on the present invention to solve basically the same technical problems and achieve basically the same technical effects are all included in the protection scope of the present invention.
Claims
1. A composite high temperature resistant filter felt, characterized in that: The following structural layers are included: Base fabric layer: woven from basalt fiber and polyimide fiber, with a gram weight of 400g / m²-600g / m²; Composite material layer: Ceramic fiber, silicon carbide nanowire and polytetrafluoroethylene modified fiber are compounded on both sides of the base fabric layer through gradient needle punching process. The total weight of the composite material layer is 200g / m²-350g / m²; Surface functional layer: It is composed of a coating of polytetrafluoroethylene emulsion and silicon carbide nanoparticles, with a thickness of 5μm-15μm and a surface pore size of 0.5μm-2μm.
2. The composite high temperature resistant filter felt according to claim 1, characterized in that: The weight ratio of basalt fiber to polyimide fiber in the base fabric layer is 3:1-5:1, and the fiber fineness is 1.5D-3D.
3. The composite high temperature resistant filter felt according to claim 1, characterized in that: The components of the composite material layer include, by weight: 40-60 parts of ceramic fibers, 10-20 parts of silicon carbide nanowires, 20-30 parts of polytetrafluoroethylene modified fibers, 1-3 parts of silane coupling agents, and 0.5-1 parts of dispersants.
4. The composite high temperature resistant filter felt according to claim 1, characterized in that: The polytetrafluoroethylene modified fiber is a product of PPS fiber impregnated with polytetrafluoroethylene emulsion, and the impregnation liquid rate is 50%-120%.
5. The composite high temperature resistant filter felt according to claim 1, characterized in that: The particle size of the silicon carbide nanoparticles in the surface functional layer is 50-200 nm, and the solid content of the polytetrafluoroethylene emulsion is 55-65 wt %.
6. The method for preparing the composite high temperature resistant filter felt according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Preparation of base fabric: basalt fiber and polyimide fiber are blended and woven into base fabric, and subjected to heat setting treatment at a temperature of 200°C-250°C for 5min-10min; S2. Pretreatment of the composite material layer: After mixing the ceramic fiber, silicon carbide nanowire and polytetrafluoroethylene modified fiber, the surface of the ceramic fiber is activated by plasma at a power of 200W-400W for 3-5min. S3, gradient needling composite: Lay the pretreated composite material layer on both sides of the base fabric, and perform pre-needling and main needling in sequence, with a pre-needling density of 300 times / cm²-500 times / cm² and a main needling density of 800 times / cm²-1000 times / cm²; S4. Surface functional layer coating: Mix polytetrafluoroethylene emulsion and silicon carbide nanoparticles and spray them on the surface of the composite material layer. After drying at 100°C-120°C, sinter at a high temperature of 300°C-350°C for 2min-5min to obtain filter felt.
7. The method for preparing a composite high temperature resistant filter felt according to claim 6, characterized in that: The gas for the plasma treatment is a mixed gas of argon and oxygen with a volume ratio of 4:
1.
8. The method for preparing a composite high temperature resistant filter felt according to claim 6, characterized in that: The weight ratio of the polytetrafluoroethylene emulsion to the silicon carbide nanoparticles is 10:1-15:1, and the spraying pressure is 0.3MPa-0.5MPa.
9. The method for preparing a composite high temperature resistant filter felt according to claim 6, characterized in that: It also includes an impregnation enhancement treatment: the composite filter felt is impregnated in a dispersion containing silica sol, the silica sol concentration is 5%-10%, the impregnation time is 10min-20min, and then it is cured at a high temperature of 250℃-280℃ for 3min-5min.
Citation Information
Patent Citations
Surface treatment method for basalt fibre
CN101125738A
Polyimide fiber composite high-temperature-resisting filter felt and preparation method thereof
CN103706184A
Preparation method of porous basalt fibers
CN105506782A
Inorganic particle / polytetrafluoroethylene composite hydrophobic wear-resistant coating and preparation method thereof
CN113248986A
High-temperature composite filter material
CN202179905U